Chemotherapy-induced prospective memory impairment in breast cancer patients with different hormone receptor expression. Issue 13 (March 2017) - Li, Wen; Gan, Chen; Lv, Yue; Wang, Shanghu; Cheng, Huaidong
Abstract : Abstract: This study aimed to investigate prospective memory impairment in patients with breast cancer with different expression of hormone receptors, including the estrogen receptor (ER) and the progesterone receptor (PR). A total of 120 patients with breast cancer who underwent chemotherapy following surgery were divided into 2 groups. The A group included 60 patients with ER − /PR − status, and the B group included 60 patients with ER + /PR + status. After 6 cycles of postoperative adjuvant chemotherapy, all patients were administered neuropsychological and prospective memory tests, such as the Mini-Mental State Examination (MMSE), verbal fluency test (VFT), and digit span test (DST), as well as examination of event-based prospective memory (EBPM) and time-based prospective memory (TBPM). As the neuropsychological background test results showed, there were no significant differences in MMSE, DST, and TBPM scores (*: P  > 0.05) between patients with breast cancer in the ER − /PR − and ER + /PR + groups, while the VFT and EBPM scores were significantly greater in patients with breast cancer with ER + /PR + status than in those with ER − /PR − status (**: P  < 0.01), indicating that patients with ER − /PR − status have significant impairment in EBPM, although not in TBPM. The results of the present study indicate that different hormone receptor expression in patients with breast cancer may be associated with heterogeneity of chemotherapy-induced prospective memory impairment.